Application Of Video-Assisted Problem Based Learning Models To Improve Student Learning Outcomes On Virus Material - yuli ananda; Hafnati Rahmatan; Samingan; Ismul Huda; Mudatsir (Universitas Serambi Mekkah, 2024)
Learning in the era of globalization directs teachers to use learning models that are adapted to existing technological media. Based on the data obtained, there is still a learning process that has not maximized the use of technological media as a tool, so students have difficulty understanding biology material which results in a lack of activity and student learning outcomes in class. The aim of this research is to determine the difference in improving student learning outcomes between the control class and the experimental class in implementing the video-assisted Problem Based Learning model on virus material. The research method used was Quasi-Experiment with a non-randomized control group type, pretest-posttest only design. The research subjects consisted of odd semester students. The research was carried out at two different Madrasah Aliyah in Aceh Besar, where Madrasah Aliyah A consisted of 61 students and Madrasah Aliyah B consisted of 60 students. The test given is a multiple choice test with 35 questions with 5 alternative answer choices. The research results showed that the average N-gain for the experimental class was 62.31 in the medium category, while the control class was 42.95, indicating the medium category. Even though it is included in the medium category, the average N-gain value for the experimental class is higher than the control class. Based on the average posttest score, the experimental class obtained a score of 73.34, higher than the control class which was only 60.59. The difference in mean posttest scores between the experimental class and the control class shows an increase in learning outcomes.